Implementation of TPA (Third Party Access) principle in Polish energy sector; Realizacja zasady TPA (Third Party Access) w polskiej elektroenergetyce - Aleksandra Lech (Comparative Economic Research. Central and Eastern Europe, 2010)
The liberalization of energy sector in Poland is conducted according to the conclusions deriving from the criticism of the traditional theory of regulation - the TPA principle is an instrument enabling introducing competition in energy trade subsector. However, in spite of formal assurance that the right to change electricity supplier is granted to all recipients, only a small number of entitled entities exercise this privilege. It is only the group of big industrial buyers among whom growing interest to exercise the TPA principle can be observed. The barriers to changing electricity supplier include economic, technical and formal ones. Removing them in the future will result in the increase of competition scale in energy sector. – – Liberalizacja sektora energoelektrycznego w Polsce przebiega zgodnie z wnioskami płynacymi z krytyki tradycyjnej teorii regulacji - zasada TPA, nakładajaca na własćicieli sieci obowiazek udostepnienia tej sieci innym podmiotom, jest instrumentem umozl̇iwiajacym wprowadzenie konkurencji w sferze obrotu energia. Jednakzė, mimo formalnego zapewnienia wszystkim odbiorcom prawa do zmiany sprzedawcy energii, niewielka liczba uprawnionych podmiotoẃ korzysta w Polsce z przywileju zmiany sprzedawcy. Jedynie wsŕod́ duzẏch odbiorcoẃ przemysłowych, obserwuje sie coraz wieksze zainteresowanie wykorzystaniem zasady TPA. Przeszkoda w zmianie sprzedawcy energii jest szereg barier ekonomicznych, technicznych i formalnych. Ich usuniecie pozwoli w przyszłosći na wzrost stopnia konkurencji w sektorze elektroenergetycznym.
Keywords: 330